2007
DOI: 10.1143/jpsjs.76sa.33
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Metallization of Molecular Crystal BI3

Abstract: We have measured the electrical resistivity up to 26 GPa to investigate the pressure-induced metallization of BI 3 . At room temperature, the resistivity decreased rapidly with applying pressure. The pressure dependence of the electrical resistance indicated metallization of BI 3 above 16 GPa. We found that the metallization in BI 3 occurs at higher pressure than that of molecular dissociation reported by our previous X-ray diffraction measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…15 Resistivity measurements showed that the new phase turned metallic at 23 GPa and exhibited superconductivity above 27 GPa. [15][16][17] The pressure dependence of T c was positive, changing from 0.5 to 1.9 K between 27 and 65 GPa. Because the atomic X-ray scattering power of boron is less than that of iodine, boron atoms were not detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Resistivity measurements showed that the new phase turned metallic at 23 GPa and exhibited superconductivity above 27 GPa. [15][16][17] The pressure dependence of T c was positive, changing from 0.5 to 1.9 K between 27 and 65 GPa. Because the atomic X-ray scattering power of boron is less than that of iodine, boron atoms were not detected.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Furthermore, some iodide crystals (such as molecular crystals BI 3 and SnI 4 ) are also reported to experience a structural phase transition, metallization, and superconductivity under pressure. [15][16][17][18][19] Insight into superconductivity under pressure can be obtained either from the conventional Eliashberg theory 20 or from the non-traditional approach of local electron-electron interactions that have been successfully applied to nanosystems and organic molecules. 21 It is inspiring that the separate condensation of electron charge and spin degrees provides a new route for superconductivity.…”
Section: Introductionmentioning
confidence: 99%